SURVEI TINGKAT KEBUGARAN JASMANI PESERTA EKSTRAKURIKULER OLAHRAGA DI SMPN 17 MALANG - Proboningrum Wuragil Kuning; Eko Hariyanto (Jayabama: Jurnal Peminat Olahraga, 2024)
Physical fitness is very important for everyone, especially for carrying out daily activities well without feeling too tired. This study aims to determine the level of physical fitness of extracurricular sports participants at SMPN 17 Malang. The method used is a quantitative descriptive survey involving 60 students as samples. Data was collected using the Indonesian Student Fitness Test (TKSI) phase D which includes several tests (1) hand and coordination test, (2) sit-up test, (3) Standing Broad Jump Test, (4) T-test, (5) beep test. Descriptive statistical techniques presented in percentage form were used in this research. The research results show overall of the 60 participants, 3 students were classified as very good, 31 students were classified as good, 20 students were classified as moderate, 5 students were classified as poor, and 1 student was classified as very poor. From these results, it is concluded that extracurricular sports participants at SMPN 17 Malang have physical fitness in the "moderate" category. Therefore, efforts need to be made to improve their body fitness so that they can achieve better achievements in the future.